2018
DOI: 10.1186/s13287-018-1039-2
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning of bone marrow-derived mesenchymal stem cells highly strengthens their potential to promote IL-6-dependent M2b polarization

Abstract: BackgroundDuring the last decade, mesenchymal stem cells (MSCs) have gained much attention in the field of regenerative medicine due to their capacity to differentiate into different cell types and to promote immunosuppressive effects. However, the underlying mechanism of MSC-mediated immunoregulation is not fully understood so far. Macrophages are distinguished in classical activated, pro-inflammatory M1 and alternatively activated M2 cells, which possess different functions and transcriptional profiles with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
115
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(140 citation statements)
references
References 49 publications
6
115
0
Order By: Relevance
“…Co-culture of hMSC-laden GFOGER-functionalized gels and macrophages upregulated macrophage secretion of the cytokine IL-10, a potent anti-inflammatory factor, compared with all other gel conditions. hMSCs have been shown to promote IL-6 dependent macrophage polarization toward an anti-inflammatory IL-10 producing phenotype 50,54 , consistent with the increased hMSC secretion of IL-6 and increased macrophage secretion of IL-10 seen in our experiments. These results indicate that integrinspecific hydrogels alter the hMSC secretome and result in functional differences in hMSC-immune cell interactions.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Co-culture of hMSC-laden GFOGER-functionalized gels and macrophages upregulated macrophage secretion of the cytokine IL-10, a potent anti-inflammatory factor, compared with all other gel conditions. hMSCs have been shown to promote IL-6 dependent macrophage polarization toward an anti-inflammatory IL-10 producing phenotype 50,54 , consistent with the increased hMSC secretion of IL-6 and increased macrophage secretion of IL-10 seen in our experiments. These results indicate that integrinspecific hydrogels alter the hMSC secretome and result in functional differences in hMSC-immune cell interactions.…”
Section: Resultssupporting
confidence: 89%
“…hMSC secretion of monocyte recuritment cytokine MCP-1 and IL-6 were also increased in vitro. In agreement with previous studies, IL-6 secreting hMSC promoted macrophage polarization toward an anti-inflammatory IL-10 producing phenotype in vitro 50,54 . The host receptor for MCP-1, CCR2, was also upregulated in GFOGER-presenting hydrogels in vivo.…”
Section: Discussionsupporting
confidence: 92%
“…Recent publications suggest an enhanced immunosuppressive effect of MSCs that were preactivated with TNF‐α, IFN‐γ, or IL‐1β . Interestingly, the improved immunomodulatory effect of preactivated MSCs has to a large extent been attributed to their superior paracrine activity with an increased secretion of immunomodulatory molecules, which does not provide a sufficient explanation for the beneficial effect of secretome‐deficient HI‐MSCs in our sepsis model.…”
Section: Discussionmentioning
confidence: 75%
“…BMSC secretion of IL-6 has been reported to skew monocyte differentiation from CD14 − CD1a + DCs to CD14 + CD1a − cells (which have a lower immunostimulatory capacity towards anti-inflammatory macrophage differentiation) [51]. Using mouse macrophages lacking α chain of IL-6 receptor, Philipp et al suggested that IL-6 signaling is indispensable for alternative activation of macrophages by BMSC coculture or IL-4 treatment [52]. Therefore, we hypothesized that aBMSCs have immunomodulatory effects on monocytes and macrophages similar to BMSCs.…”
Section: Discussionmentioning
confidence: 99%